DEVELOPMENT AND EVALUATION OF MUCOADHESIVE BILAYER GASTRORETENTIVE TABLETS OF TRIMETAZIDINE DIHYDROCHLORIDE AND IVABRADINE HYDROCHLORIDE - SAGAR S. JADHAV; ATUL A. PHATAK (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The objective of the present investigation was to combine ivabradine hydrochloride (IBH) and trimetazidine dihydrochloride (TMZ) in bilayer mucoadhesive gastroretentive tablets for effective treatment of angina, reduce multiple dosing, and to discover best alternative to conventional drug with lesser adverse effects. Methods: Bilayer gastro retentive tablets formulated using simple direct compression method and mucoadhesive approach wherein IBH incorporated in immediate release (IR) while TMZ as mucoadhesive layer. Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and melting point and ultraviolet (UV) spectroscopy performed to evaluate compatibility and purity of active pharmaceutical ingredient (API). IBH IR layer prepared using Avicel-112, Vivasol, Klucel and TMZ mucoadhesive layer developed using Benecel K200M, Kollidon SR, Xanthan gum, and stearic acid. Bilayer tablets prepared with simple direct compression and evaluated for physical parameters, in vitro dissolution, mucoadhesive strength, % swelling index, stability study for 6 months, and in vivo study conducted in New Zealand white rabbits using barium sulfate in TMZ tablets. Results: DSC, FTIR, UV spectroscopy, and melting point confirmed the purity of both the API and their compatibility. IBH IR layer quickly disintegrated within 5 s and released complete drug. TMZ mucoadhesive layer controlled release up to 12 h with 51.15 N mucoadhesive strength. Tablet remained unchanged after 6 months stability study at 40°C–75% temperature-RH condition. Furthermore, X-ray imaging study for 24 h confirmed that TMZ tablet retained in rabbit stomach for more than 12 h. Conclusion: Based on stability study, results and in vivo testing it was concluded that IBH and TMZ mucoadhesive bilayer tablets successfully developed using simple direct compression. Further optimization required to control the drug release and to increase gastric retention time.